Pragmatic Trials and Improving Long‐Term Care: Recommendations From a National Institutes of Health Conference. Issue 3 (23rd February 2022) - Zimmerman, Sheryl; Resnick, Barbara; Ouslander, Joseph; Levy, Cari; Gaugler, Joseph E.; Sloane, Philip D.; Mor, Vincent
Abstract : See related Special Articles by Gurwitz el al . and Levy et al . and Resnick et al . in this issue.